Rejestracja i ochrona domen internetowych a problemy prawne - Sikora, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article addresses modern struggles related to domain law and abusive domain registrations. It discusses the idea behind growing International and US legislation which amounts to fight against phenomenon as cybersquatting or passive domain registration. Also, the article addresses the newly growing area of polish law which is, by now, full of uncertainties concerning domain law classification.
Keywords: domain law; cybersquatting; abusive domain registration; law of new technologies; property law